Perlindungan Hukum Kreditor Preferent Pada Perusahaan Asuransi Yang Pailit - Tri Reni Novita; M. Faisal Husna (Inovasi Pratama Internasional. Ltd, 2023)
Legal protection for policyholders, insured or insurance participants, in relation to insurance company bankruptcy, Indonesian positive law has actually provided a way out with several alternative options, namely based on the provisions of the Civil Code, the Bankruptcy Law, and the provisions of the Indonesian Civil Code. Law No.40 of 2014 stipulates explicitly that the rights of the policyholder/insured or insurance participant for the distribution of the assets of an insurance company bankrupt by court or liquidation have a higher (primary) position than the rights of other creditors. Article 52 paragraph (1) states “In the event that an insurance company, sharia insurance company, reinsurance company or sharia reinsurance company is bankrupt or liquidated, the rights of the policyholder, the insured or participants for the distribution of their assets have a higher position than the rights of other parties”. The meaning of this sentence is thar the policyholder has a position as a preferred creditor, namely a creditor whose position takes precedence over other creditors in the distribution of bankruptcy assets of an insurance company. In the distribution of bankruptcy assets, the policyholder has the right to demand priority payment of his rights in accordance with the previously agreed agreement.